I love you, Ronnie the letters of Ronald Reagan to Nancy Reagan - Reagan, Nancy 1921-2016; Reagan, Ronald 1911-2004 (Random House, 2000)
Through letters and reflections, the characters, personalities, and private lives of a president and his first lady are revealed. Nancy Reagan comments on the letters and writes with love and insight about her husband and the many phases of their life together.